Reading comprehension is modulated by lexical-semantic knowledge in skilled and less-skilled comprehenders - Bender de Sousa, Lucilene; Hübner, Lilian Cristine; Covatti Malcorra, Bárbara Luzia (Calidoscópio, 2022)
This study aimed at examining the depth of vocabulary knowledge, lexical-semantic processing and implicit semantic memory in SCs and L-SCs. The participants were 86 eighth-graders from public schools in the south of Brazil, tested with tasks of word definition, semantic judgment, and lexical decision. Results showed that SCs and L-SCs differed significantly in the depth of vocabulary knowledge and lexical-semantic processing but not in the implicit semantic memory. Although it is not clear if L-SCs present lexical-semantic knowledge delay or deficit, the results are more consistent with the hypothesis of a delay. They also suggest that lexical-semantic knowledge and processing may be an important path for intervention with L-SCs. Keywords: reading; comprehension; vocabulary; semantic; priming.